Testing an empathy model of guest-directed citizenship and counterproductive behaviours in the hospitality industry: findings from three hotels - Ho, Violet T. (2013)
This research proposes and tests an empathy model of guest-directed discretionary behaviours (i.e., citizenship and counterproductive behaviours) using two studies conducted in three hotels. Building on the two-stage model of empathic mediation, we examined the mediating role of empathic concern in the relationship between perspective taking and both forms of discretionary behaviours in Study 1. Support for this mediated model was found in relation to citizenship behaviours but not for counterproductive behaviours. Study 2 was conducted to extend these findings using peer reports of discretionary behaviours, and to apply an interactional psychology perspective to predict guest-directed counterproductive behaviours. We drew upon trait activation theory to highlight the importance of situational triggers, in the form of interpersonal injustice from guests, in moderating the relationship between perspective taking and counterproductive behaviours, mediated through empathic concern. We found support for the hypothesized moderated mediation effect, such that perspective taking inhibited counterproductive behaviours through empathic concern only when interpersonal injustice was high, but not when injustice was low. Replicating the results in Study 1, perspective taking also positively predicted peer-reported citizenship behaviours, but this was not mediated by empathic concern. Research and practical implications from these findings are discussed.